2019
DOI: 10.18632/aging.102575
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed methyltransferase-like 1 (METTL1) increased chemosensitivity of colon cancer cells to cisplatin by regulating miR-149-3p/S100A4/p53 axis

Abstract: Methyltransferase-like 1 (METTL1) mediated 7-methylguanosine (m7G) is crucial for the regulation of chemoresistance in cancer treatment. However, the role of METTL1 in regulating chemoresistance of colon cancer (CC) cells to cisplatin is still unclear. This study established the cisplatin-resistant CC (CR-CC) cells and found that METTL1 was low-expressed in CR-CC cells compared to their paired cisplatin-sensitive CC (CS-CC) cells. Besides, overexpressed METTL1 enhanced the cytotoxic effects of cisplatin on CR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 28 publications
3
91
0
Order By: Relevance
“…Therefore, in the present study, we identi ed a novel circRNA, hsa_circRNA_103809, that regulated cisplatin-resistance in NSCLC. Mechanistically, according to the previous publications [35,36], the cisplatin-resistant NSCLC (CR-NSCLC) cells were inducted from their corresponding parental cisplatin-sensitive NSCLC (CS-NSCLC) cells, and we found that hsa_circRNA_103809 tended to be high-expressed in CR-NSCLC cells, compared to CS-NSCLC cells. Interestingly, further experiments evidenced that knock-down of hsa_circRNA_103809 enhanced the inhibiting effects of cisplatin on cell proliferation and viability in CR-NSCLC cells.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, in the present study, we identi ed a novel circRNA, hsa_circRNA_103809, that regulated cisplatin-resistance in NSCLC. Mechanistically, according to the previous publications [35,36], the cisplatin-resistant NSCLC (CR-NSCLC) cells were inducted from their corresponding parental cisplatin-sensitive NSCLC (CS-NSCLC) cells, and we found that hsa_circRNA_103809 tended to be high-expressed in CR-NSCLC cells, compared to CS-NSCLC cells. Interestingly, further experiments evidenced that knock-down of hsa_circRNA_103809 enhanced the inhibiting effects of cisplatin on cell proliferation and viability in CR-NSCLC cells.…”
Section: Discussionmentioning
confidence: 71%
“…The Roswell Park Memorial Institute 1640 medium (RPMI-1640, HyClone, USA) containing 10% fetal bovine serum (FBS, Gibco, USA). According to the experimental procedures provided by the previous work [35,36] and our preliminary experiments (data not shown), the CS-NSCLC cells were exposed to continuous low-dose cisplatin stimulation, ranged from 0.5 Îźg/ml to 5 Îźg/ml, for 80 days in a step-wise manner to generate descendent CR-NSCLC cells (A549/DDP, H1299/DDP and Calu-3/DDP). After that, the CR-NSCLC cells were stimulated with high-dose cisplatin (25 Îźg/ml) for 0 h, 24 h, 48 h and 72 h, to validate the successful induction of CR-NSCLC cells.…”
Section: Cell Culture and Induction Of Cisplatin-resistant Nsclc (Cr-mentioning
confidence: 99%
“…The NSCLC cells were subjected to differential treatments, and the TRIzol reagent (Invitrogen, USA) was employed to extract the total RNA. Next, the Real-Time qPCR was conducted to determine the expression levels of hsa_circRNA_103809, miR-377-3p and GOT1 mRNA, and the experimental procedures had all been documented in the previous publications [35,36]. Of note, to detect hsa_circRNA_103809 levels, the total RNA must be pre-treated with RNase R enzyme (3 U/Îźg) for 20 min at 37 ℃ to eliminate linear RNA.…”
Section: Real-time Qpcrmentioning
confidence: 99%
See 2 more Smart Citations